Endometrial assessment in cases of primary infertility in women: a prospective study - Patil, Soumya R.; Patil, Rajesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Worldwide Infertility rate prevails around 8-12% of all couples; approximately 80 million are infertile. In India 10-15% of couples are infertile. Investigating for infertility is to intervene into the modifiable/treatable causes. Therefore, the present study has been undertaken to investigate the morphological patterns of endometrial tissue in women with primary infertility. Methods: The study included 60 cases with complaints of infertility (primary). The premenstrual D and C was done to obtain endometrial biopsy. The present prospective study was a descriptive study and the values are mentioned in percentages. Results: In present study a total of 60 cases were studied. Out of which 36 cases (60%) belonged to the young adult age group. The predominant morphological pattern was that of secretory endometrium seen in 22 cases (36.66%) as opposed to proliferative, endometritic or tubercular pattern. The predominant menstrual pattern recorded was regular; seen in 41 cases (68.33%) as opposed to irregular or mennorhagic patterns. Conclusions: The endometrial biopsy has a great role in screening the cases of infertility as it helps to assess the information about ovulation, ripening of the endometrial tissue and other abnormal endometrial reaction, hormonal imbalance. This is the only method to label the diagnosis of endometrial tuberculosis in an apparently healthy female.